Hank The Cowdog: Every Dog Has His Day - Book 10 - Erickson, John R., 1943-; Holmes, Gerald L. (Austin, Texas : Texas Monthly Press, 1989)
Hank the cowdog gets into more and more trouble before he is able to find a happy solution to his problems.
"A Maverick book"--P. [4] of cover.
Keywords: Dogs -- Fiction; Dogs -- Fiction; Humorous Stories; West (U.S.) -- Fiction